EGFL7 expression profile in IDH-wildtype glioblastomas is associated with poor patient outcome - Da Costa, Bruno Henrique Bressan; Becker, Aline Paixao; Neder, Luciano; Goncalves, Paola Gyuliane [UNESP]; De Oliveira, Cristiane [UNESP]; Polverini, Allan Dias; Clara, Carlos Afonso; Teixeira, Gustavo Ramos; Reis, Rui Manuel; Bidinotto, Lucas Tadeu [UNESP] (The Korean Society of Pathologists and The Korean Society for Cytopathology, 2022)
Background: Despite the advances in glioblastoma (GBM) treatment, the average life span of patients is 14 months. Therefore, it is urgent to identity biomarkers of prognosis, treatment response, or development of novel treatment strategies. We previously described the association of high epidermal growth factor-like domain multiple 7 (EGFL7) expression and unfavorable outcome of pilocytic astrocytoma patients. The present study aims to analyze the prognostic potential of EGFL7 in GBM isocitrate dehydrogenase (IDH)-wildtype, using immunohistochemistry and in silico approaches. Methods: Spearman's correlation analysis of The Cancer Genome Atlas RNA sequencing data was performed. The genes strongly correlated to EGFL7 expression were submitted to enrichment gene ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Additionally, EGFL7 expression was associated with patient overall survival. The expression of EGFL7 was analyzed through immunohistochemistry in 74 GBM IDH-wildtype patients' samples, and was associated with clinicopathological data and overall survival. Results: In silico analysis found 78 genes strongly correlated to EGFL7 expression. These genes were enriched in 40 biological processes and eight KEGG pathways, including angiogenesis/vasculogenesis, cell adhesion, and phosphoinositide 3-kinase-Akt, Notch, and Rap1 signaling pathways. The immunostaining showed high EGFL7 expression in 39 cases (52.7%). High immunolabelling was significantly associated with low Karnofsky Performance Status and poor overall survival. Cox analysis showed that GBMs IDH-wildtype with high EGFL7 expression presented a higher risk of death compared to low expression (hazard ratio, 1.645; 95% confidence interval, 1.021 to 2.650; p = .041). Conclusions: This study gives insights regarding the genes that are correlated with EGFL7, as well as biological processes and signaling pathways, which should be further investigated in order to elucidate their role in glioblastoma biology.
Keywords: EGFL7; Glioblastoma IDH-wildtype; Notch pathway; PI3K-Akt pathway; Rap1 pathway